2022
DOI: 10.3389/fcell.2022.887100
|View full text |Cite
|
Sign up to set email alerts
|

Vangl as a Master Scaffold for Wnt/Planar Cell Polarity Signaling in Development and Disease

Abstract: The establishment of polarity within tissues and dynamic cellular morphogenetic events are features common to both developing and adult tissues, and breakdown of these programs is associated with diverse human diseases. Wnt/Planar cell polarity (Wnt/PCP) signaling, a branch of non-canonical Wnt signaling, is critical to the establishment and maintenance of polarity in epithelial tissues as well as cell motility events critical to proper embryonic development. In epithelial tissues, Wnt/PCP-mediated planar pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 146 publications
0
19
0
Order By: Relevance
“…VANGLs also bind to DVL ( 19 , 20 ), and studies have shown that the interaction of de novo synthesized VANGLs with DVL promotes efficient recruitment of DVL from the endoplasmic reticulum to the plasma membrane, whereas the complex inhibits interaction of DVL with its downstream effector DAAM1 (Dishevelled-associated activator of morphogenesis 1) that promotes RHOA activation ( 21 ). At the apical plasma membrane, DVL is transferred from VANGL to FZD and thereby stimulates FZD-DVL complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…VANGLs also bind to DVL ( 19 , 20 ), and studies have shown that the interaction of de novo synthesized VANGLs with DVL promotes efficient recruitment of DVL from the endoplasmic reticulum to the plasma membrane, whereas the complex inhibits interaction of DVL with its downstream effector DAAM1 (Dishevelled-associated activator of morphogenesis 1) that promotes RHOA activation ( 21 ). At the apical plasma membrane, DVL is transferred from VANGL to FZD and thereby stimulates FZD-DVL complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, epithelial cells exhibit two-way polarity: polarity along the apical-basal axis and that across the plane of the epithelial sheet. The latter is referred to as PCP, an essential property for regulating epithelial tissue integrity and its developmental process [7]. The airway epithelial surface is lined with numerous ciliated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Frizzled and Dishevelled are core PCP proteins that constitute the Wnt signaling pathway. There are three main Wnt pathways: the canonical b-catenin-dependent pathway, the noncanonical Wnt/calcium pathway, and the noncanonical Wnt/PCP pathway [7,9]. The last pathway plays a critical role in PCP formation, and has been investigated in various organs and tissues, such as epithelial tissue [10], lung [9], cochlea [11,12], bile duct [13], kidney [14,15], vasculature [16], neural tube/crest [11,[17][18][19], gastrula [17], and malignant tumors [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations